Exploration of STEAM learning in Nigeria and Indonesia for primary school student - Israel Olaofe, Abayomi; Hadi Wibowo, Amiruddin (EduStream: Jurnal Pendidikan Dasar, 2025)
In the era of the industrial revolution 4.0, the STEAM learning approach is very important to form a generation that is not only academically intelligent but also creative, collaborative, and adaptive since elementary school level. However, the implementation of STEAM learning in developing countries such as Nigeria and Indonesia still faces various challenges, ranging from limited resources, teacher readiness, to suboptimal policy support. This study aims to explore in depth the experiences of teachers, the learning strategies applied, and the obstacles they face in implementing the STEAM approach in elementary schools in both countries. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with teachers and principals who are actively involved in STEAM learning practices. Data were analyzed using NVivo software to identify key themes that emerged from informant narratives. The results of the study indicate that teachers in Nigeria and Indonesia have begun to implement STEAM contextually with a project-based approach, but its implementation is still limited due to lack of training, limited media and learning aids, and school policies that do not fully support it. In conclusion, the success of STEAM implementation in primary schools is highly dependent on strengthening teacher capacity through ongoing training, provision of learning resources relevant to the local context, and support from an education system that is adaptive to the needs of cross-disciplinary learning in developing countries.